Legal Basis for the Involvement of Counselors in the Diversion Process Literature Review Based on the Juvenile Criminal Justice System Law and Counseling Practice - Muhammad Yogie Adha Yogie; Komariah Komariah (Sean Institute, 2026)
The phenomenon of juvenile delinquency that develops within society reflects a complex issue involving individual, family, and social environmental factors. Children in conflict with the law require a more humanistic legal approach that emphasizes recovery rather than mere punishment. In Indonesia, Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (JCJS Law) introduces the diversion mechanism as an implementation of restorative justice, aiming to shift the settlement of juvenile cases from formal judicial proceedings to non-penal measures. This paper aims to examine the legal basis for the involvement of counselors in the diversion process by employing a normative juridical research method through statutory and literature approaches. The findings indicate that, although the role of counselors is not explicitly stated in the Juvenile Criminal Justice System Law, the inclusive legal provisions within Indonesia’s Law No. 11 of 2012, Government Regulation No. 65 of 2015, and Supreme Court Regulation No. 4 of 2014 provide opportunities for counselors to participate as professional actors in the diversion process. Counselors hold a strategic role in facilitating the psychological and social recovery of both juvenile offenders and victims through guidance and counseling services that focus on emotional regulation, trauma healing, and moral responsibility development.